1989
DOI: 10.1128/jvi.63.8.3529-3534.1989
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional termination between bovine papillomavirus type 1 (BPV-1) early and late polyadenylation sites blocks late transcription in BPV-1-transformed cells

Abstract: Bovine papillomavirus type 1 (BPV-1) is a small DNA tumor virus which induces fibropapillomas in cattle and transforms rodent cells in culture. Transcripts are derived from a single strand of the circular viral genome, which has multiple promoters and two polyadenylation sites. In the transformed cell, the first (early) polyadenylation site is utilized exclusively and, therefore, only the early region is expressed. Transcription of the late genes, which requires use of the second (late) polyadenylation site, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 34 publications
(40 reference statements)
1
10
0
Order By: Relevance
“…Sequences which mediate instability of heterologous transcripts have been identified in the 3Ј UTR sequences of BPV-1, HPV-1, and HPV-16 (14,26,46). In addition, transcription termination sites have been identified in the L2 gene of BPV-1 (6). Any combination of these mechanisms could function in a differentiation-dependent manner to allow for the appearance of transcripts encoding L1/L2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequences which mediate instability of heterologous transcripts have been identified in the 3Ј UTR sequences of BPV-1, HPV-1, and HPV-16 (14,26,46). In addition, transcription termination sites have been identified in the L2 gene of BPV-1 (6). Any combination of these mechanisms could function in a differentiation-dependent manner to allow for the appearance of transcripts encoding L1/L2.…”
Section: Discussionmentioning
confidence: 99%
“…A differentiation-dependent reduction in CstF function would result in inefficient polyadenylation of early HPV-31 transcripts and increased read-through into the late region. Since messages encoding L1 and L2 are regulated by multiple posttranscriptional mechanisms, including RNA instability mediated through cis elements and transcription termination sites, it is difficult to study the efficiency of early polyadenylation in the context of the complete HPV-31 genome (6,14,26,46). For these reasons, we developed a reporter assay to determine whether the efficiency of HPV-31 early polyadenylation was altered during epithelial differentiation.…”
Section: Hpv-31 Transcripts Using the Early Polyadenylation Signal Comentioning
confidence: 99%
“…Poly(A)-assisted termination is indicated whenever transcription continues for a considerable distance (e.g., from 500 bp up to several kilobases) past the poly(A) site with little or no decline (5, 10, 18-20, 27, 29, 34, 39, 43, 44, 54, 60, 62, 68). Subsequent termination may then be precipitous (10,20,34,39,62) or gradual (5,27,29,60,62), depending on the nature or presence of any terminator. On the other hand, poly(A)driven termination cannot be unambiguously identified in the absence of experiments that demonstrate efficient DNA sequence-independent termination downstream of the poly(A) site.…”
Section: Discussionmentioning
confidence: 99%
“…The BPV‐1 genome has two PASs, the proximal PAS and the distal PAS. The proximal PAS is located between the early genes and the late genes, and the distal PAS is located at the 3′ end of the late genes (Figure (a)) . Furth et al found a short sequence located just upstream of the distal PAS that serves to downregulate the late gene expression during the early phase of infection.…”
Section: U1 Snrnp Inhibits 3′‐end Processingmentioning
confidence: 99%